PERENCANAAN FASILITAS OBJEK WISATA TOBEK PABOUN DI DESA PEBAUN HILIR KECAMATAN KUANTAN MUDIK PROVINSI RIAU - Aprilia, Novi; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to analyze the facility planning for the Tobek Paboun tourist attraction in Pebaun Hilir Village, Kuantan Mudik District, Riau Province. Tobek Paboun is a tourist destination offering natural beauty and local culture, but has experienced a decline in visitor numbers due to inadequate facilities. The research method used was qualitative with a descriptive approach, involving interviews, observation, and documentation. The results indicate several obstacles in facility planning, including funding and land acquisition issues. Nevertheless, the management is committed to improving the facilities by adding gazebos, homestays, and improving existing infrastructure. This study is expected to provide recommendations for managers and the government on improving the Tobek Paboun tourist attraction to make it more attractive to tourists. Keywords: Facility Planning, Tourist Attraction, Tobek Paboun, Pebaun Hilir Village, Nature Tourism.